Hubungan Pengetahuan Dan Sikap Terhadap Kepatuhan Konsumsi Tablet Fe Pada Ibu Hamil Trimester III Di Puskesmas Sumbang II - Diah Atmarina Yuliani; Siti Maesaroh (2023)
Adequacy of iron in pregnant women themselves can be fulfilled by getting blood added tablets (TTD) of at least 90 tablets during pregnancy. However, in fact, the field is still found mothers who do not comply in taking tablets due to several factors such as knowledge and attitude of mothers to Fe tablets. This study aims to determine the relationship of knowledge and attitudes towards compliance Fe tablet consumption in pregnant women in the third trimester II Puskesmas Sumbang. This type of research is Quantitative that uses analytical observational design with cross sectional approach. A sample of 89 mothers with purposive sampling technique. Data collection using questionnaires. Analysis using chi square test. Results showed that the respondents were mostly well-informed respondents as many as 55 respondents (61.8%) and well-behaved as many as 65 respondents (73.0%). Respondents were mostly obedient in taking Fe tablets as many as 63 respondents (70.8%) and 26 respondents (29.2%) did not comply. Chi square test showed that there is a relationship of knowledge (p value of 0.000) and attitude (p value of 0.018) towards compliance Fe tablet consumption in pregnant women trimester III. There is a relationship of knowledge and attitude towards compliance Fe tablet consumption in pregnant women trimester III at Puskesmas Sumbang II.